2023
DOI: 10.1002/cre2.823
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, knowledge, and practices related to oral health in a group of pregnant women: A qualitative study

Juliana Velosa‐Porras,
Nelcy Rodríguez Malagón

Abstract: BackgroundIt is well known that the prevalence of dental caries and periodontal disease is increasing in pregnant women. Dental care is mostly sufficient to prevent oral diseases and perform timely interventions. However, few pregnant women go to the dental office during this period due to a lack of knowledge. The perceptions, knowledge, and oral health practices of pregnant women have been scarcely explored and should be taken into account to propose positive interventions in this population.ObjectivesTo iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…8 Correct knowledge and perception were identified as key predictors to the adoption of good oral health practices as well as maintaining regular dental visits among pregnant women. 9 However, studies conducted among pregnant women have always reported lack of proper oral health knowledge as well as wrong perceptions about the importance of oral health and its effects on their pregnancy and their offsprings oral and general health. [9][10][11] It was also reported that pregnant women lack the knowledge about the importance of regular dental visits and tend to avoid dental care even if they suffer from dental problems 11 mainly due to lack of knowledge and misconceptions that dental care/treatment will harm the fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Correct knowledge and perception were identified as key predictors to the adoption of good oral health practices as well as maintaining regular dental visits among pregnant women. 9 However, studies conducted among pregnant women have always reported lack of proper oral health knowledge as well as wrong perceptions about the importance of oral health and its effects on their pregnancy and their offsprings oral and general health. [9][10][11] It was also reported that pregnant women lack the knowledge about the importance of regular dental visits and tend to avoid dental care even if they suffer from dental problems 11 mainly due to lack of knowledge and misconceptions that dental care/treatment will harm the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, studies conducted among pregnant women have always reported lack of proper oral health knowledge as well as wrong perceptions about the importance of oral health and its effects on their pregnancy and their offsprings oral and general health. [9][10][11] It was also reported that pregnant women lack the knowledge about the importance of regular dental visits and tend to avoid dental care even if they suffer from dental problems 11 mainly due to lack of knowledge and misconceptions that dental care/treatment will harm the fetus. 12 In Saudi Arabia there is a continuum increase in the prevalence of adverse pregnancy outcomes 13 as well as high prevalence of periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%